2023
DOI: 10.1172/jci171468
|View full text |Cite
|
Sign up to set email alerts
|

Piezo1 agonist restores meningeal lymphatic vessels, drainage, and brain-CSF perfusion in craniosynostosis and aged mice

Matt J. Matrongolo,
Phillip S. Ang,
Junbing Wu
et al.

Abstract: Skull development coincides with the onset of cerebrospinal fluid (CSF) circulation, brain-CSF perfusion, and meningeal lymphangiogenesis, processes essential for brain waste clearance. How these processes are affected by craniofacial disorders such as craniosynostosis are poorly understood. We report that raised intracranial pressure and diminished CSF flow in craniosynostosis mouse models associate with pathological changes to meningeal lymphatic vessels that affect their sprouting, expansion, and long-term … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
6
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 52 publications
2
6
0
Order By: Relevance
“…Matrongolo et al showed that treatment of Twist1 +/– mice exhibiting CS with Yoda1 reduced ICP and improved paravascular CSF-brain influx, MLV coverage, and CSF macromolecule clearance to dcLNs ( Figure 1 ). A similar beneficial effect of Yoda1 was also observed in aged mice that had undergone atrophic and hyperplastic changes in MLVs ( 12 ). These data indicate that Piezo1 activation is beneficial in the treatment of CS-associated ICP increase and that it can also rejuvenate age-related MLV changes ( 12 , 14 ).…”
Section: Yoda1 To the Rescuesupporting
confidence: 54%
See 4 more Smart Citations
“…Matrongolo et al showed that treatment of Twist1 +/– mice exhibiting CS with Yoda1 reduced ICP and improved paravascular CSF-brain influx, MLV coverage, and CSF macromolecule clearance to dcLNs ( Figure 1 ). A similar beneficial effect of Yoda1 was also observed in aged mice that had undergone atrophic and hyperplastic changes in MLVs ( 12 ). These data indicate that Piezo1 activation is beneficial in the treatment of CS-associated ICP increase and that it can also rejuvenate age-related MLV changes ( 12 , 14 ).…”
Section: Yoda1 To the Rescuesupporting
confidence: 54%
“…A similar beneficial effect of Yoda1 was also observed in aged mice that had undergone atrophic and hyperplastic changes in MLVs ( 12 ). These data indicate that Piezo1 activation is beneficial in the treatment of CS-associated ICP increase and that it can also rejuvenate age-related MLV changes ( 12 , 14 ).…”
Section: Yoda1 To the Rescuesupporting
confidence: 54%
See 3 more Smart Citations